Proceedings IAPA International Conference and International Indonesia Conference on Interdisciplinary Studies (IICIS) - Editorial Secretary (Iapa Proceedings Conference, 2022)
Proceedings IAPA International Conference and International Indonesia Conference on Interdisciplinary Studies (IICIS)